Measuring student teachers’ beliefs regarding religion in schools: piloting and preliminary validation of two newly developed scales - Penthin, Marcus; Pirner, Manfred; Scheunpflug, Annette; Kröner, Stephan (British Journal of Religious Education, 2022)
Previous findings on religious beliefs of teachers suggest a relation between individual religiosity and professional thinking and acting of teachers. Evidence beyond faith schools and teachers with Religious Education (RE) as a subject is scarce, suitable measuring instruments are also lacking. Therefore, this paper reports the development and validation of two scales assessing teachers’ “Beliefs regarding the appropriate role of religion in the school context” and “Beliefs regarding the appropriate role of individual teachers’ religiosity”. Data from N = 348 German teacher education students were analysed. We examined reliability and validity of both scales by employing correlation analysis, confirmatory factor analysis, analysis of convergent and discriminant validity, measurement invariance analysis and structural equation modelling. For external validation, we examined the extent to which both scales are explained by the Centrality of Religiosity Scale (CRS, Huber and Huber 2012) and RE as a subject studied. Our analyses support the reliability and convergent and discriminant validity of both scales. Moreover, both scales are substantially explained by the CRS while none of them is explained by RE as subject. Thus, the piloted scales may be applied in future studies investigating the role of religiosity regarding the professional thinking and acting of teachers. <
Keywords: Religiosity; teacher beliefs; student teachers; validation study